Penjatuhan Pidana terhadap Anak Pelaku Tindak Pidana Narkotika (Kajian Putusan Nomor 118/Pid.B/2010/PN.TTN) - Nurhafifah Nurhafifah; Yusnaiti Yusnaiti (Universitas Syiah Kuala, 2012)
ABSTRACT: The Act Number 3, 1997 regarding Juvenile Court states that imprisonment and action are the punishments that can only be imposed for juvenile offenders. In the decision Number 118/Pid.B/2010/PN.TTN, the judges do not consider the imposition of punishments in accordance with Article 28 of the Act Number 3, 1997 stating that if the fine is not payable, it is replaced by obligatory working training, however the judge in its decision considers that if the fine is not payable, it is replaced by detention for 3 (three) months. In addition, the judge in its decision also doesnot provide report from resocialisation guide as it is obligatory to be considered by the judge in the decision and it is then against the law and the consequence of it is the nullification of the decision. The Conviction of Juvenile Offenders in Narcotic Crime (A Case Study on Decicion Number 118/PID.B/2010/PN.TTN)